Chronicle - Aleknavičienė, Ona; Citavičiūtė, Liucija; Čiurinskas, Mintautas; Gudmantas, Kęstutis; Meyer-Ravaitytė, Raimonda; Mocejūnaitė- Vaitkienė, Simona; Pajėdienė, Jūratė; Rekašiūtė, Kotryna; Sidabraitė, Žavinta; Šaulys, Tadas; Terleckienė, Eleonora; Vaitkevičiūtė Verbickienė, Viktorija (Senoji Lietuvos literatūra, 2024)
-